(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The first chapter included the introduction, the importance of the research, and the aim of the research to prepare special educational units using the triple peer learning method in learning some types of scoring (scoring from the free throw line - scoring by jumping - peaceful scoring). To know the effect of the triple pair learning method in learning skills in basketball. Find out which of the two groups is better at learning skills in basketball. The second chapter included the theoretical framework and related studies. The third chapter included the research methodology and field procedures, and the researcher used the experimental method. The research community reached (110) students from the second stage in the Department of Physical Education and Sports Sciences - Al-Salam University College for the academic year 2021/2022, with (3) people. As for the research sample, it was chosen in this way. Intentionally random, two divisions were chosen from the original research community, namely Division (A-C), and by drawing lots, Division (A) became (37) students for the experimental group and Division (C) (36) students for the control group, and (13) students were excluded from the two divisions (A) and (C) who did not commit to attending, and the research sample became (60) students distributed equally into the two groups, and the exploratory experiment was conducted on a sample of (10), and the percentage of the sample was (54%) from the original community The fourth chapter included presenting, analyzing and discussing the results, and included a detailed presentation of the results of all tests. The fifth chapter included the conclusions, which are: - The researcher concluded that the experimental group, which applied the triple peer learning method, was superior to the control group in learning some types of basketball scoring for students. The researcher recommends emphasizing the use of peer learning method in modern studies and practical lessons.Keywords: triple peer learning style, learning some types of basketball scoring.extracted search.